PENGEMBANGAN MEDIA MEDIVERSE ANATOMY BERBANTUAN AR DAN GAMIFIKASI UNTUK MENINGKATKAN KREATIVITAS IMAJINATIF SISWA SEKOLAH DASAR - Sulfani; Fitrianingsih, Nur; Hardiansyah; Mariamah; Ahyar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of students’ imaginative creativity in learning is often caused by the limited use of interactive learning media, especially in learning human anatomy which tends to be abstract. This study aims to develop MediVerse Anatomy learning media based on Augmented Reality (AR) and gamification to improve students’ imaginative creativity. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analyze, design, development, implementation, and evaluation stages. The subjects were fourth-grade students at SDN Inpres Rabakodo, involving 39 students in the implementation stage. Data were collected through observation, validation sheets, questionnaires, and pretest-posttest instruments. The results showed that the developed media was highly feasible with an average validation score of 88,75%. The effectiveness test indicated a moderate improvement with an N-Gain value of 0.62 and a significant difference between pretest and posttest results (p < 0.05). In addition, the practicality level reached 92.56% in the very practical category. These findings indicate that the integration of AR and gamification in MediVerse Anatomy can enhance students’ engagement, understanding, and imaginative creativity.